SOSIALISASI PENGGUNAANPROGRAM POWER POINTDAN FONT KARAKTER LONTARAQ DALAM PENGAJARAN BAHASA DAERAHPADA GURU-GURU SEKOLAH DASAR-MENENGAH DI KABUPATEN GOWA - Gusnawaty, Gusnawaty; Latjuba, Ade Yolanda; Hadrawi, Muhlis; Bandu, iriantu (JURNAL ILMU BUDAYA, 2016)
To save the local language from destruction, the Elementary and Secondary Education Curriculum should includeLocal Language as local content that must be learned. Butin reality, the teaching of Region Laguage still seemmonotonous and boring to the students of primary and secondary schools in Palangga, Gowa. To overcome thissituation, we held training sessions for teachers in order to utilize the computer as a learning medium. The trainingheld on the spot. The teachers are trained to use power point 2007 and installed Lontaraq character fonts into theircomputer, so they can improve their skill in learning to write, listen, and understand the language of the Bugis-Makassar. The proficiency is expected to be transferred when they teach their studentsKeywords: elementary and secondary school teachers; the locallanguage; lontaraqfont;power point; capabilities.